2016
DOI: 10.1080/13102818.2016.1265900
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the bacterial community in a crystallizer pond, Pomorie salterns, Bulgaria

Abstract: The aim of this study was to investigate the bacterial community habituating P18, the biggest crystallizer pond in Pomorie salterns (34% salinity). The obtained results showed that the bacterial community differs from many previous reports of low bacterial diversity in hypersaline environments and demonstrates unusually high diversity of presented taxa, some unusual domination of diverse genera not reported before as dominant and identification of previously unknown 16S rRNA sequences. The retrieved 23 bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Thus, our outcome was somehow inconsistent with the majority of results from others, but it must be taken into account that most of these regarded the Santa Pola saltern (Spain), which is considered a study model for hypersaline environments, but is located in a more southerly location than ST. Actually, for different solar salterns over the world, other authors reported quite different assemblages concerning the bacterial fraction of the prokaryotic communities, indicating possible bio-geographic patterns [ 18 , 20 , 21 , 23 , 26 , 27 , 32 , 33 , 34 , 35 , 38 , 39 ]. Among them, some studies regarding the MS of Chile, Mexico, India, Bulgaria, and Spain revealed not only the presence of Proteobacteria in the crystalliser ponds (280%–440‰ of salinity), but also that they were more abundant than Bacteroidetes [ 23 , 27 , 33 , 35 , 38 , 39 ]. In addition, in some cases, Actinobacteria was also found among the major phyla harboured by the crystallization ponds [ 32 , 33 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our outcome was somehow inconsistent with the majority of results from others, but it must be taken into account that most of these regarded the Santa Pola saltern (Spain), which is considered a study model for hypersaline environments, but is located in a more southerly location than ST. Actually, for different solar salterns over the world, other authors reported quite different assemblages concerning the bacterial fraction of the prokaryotic communities, indicating possible bio-geographic patterns [ 18 , 20 , 21 , 23 , 26 , 27 , 32 , 33 , 34 , 35 , 38 , 39 ]. Among them, some studies regarding the MS of Chile, Mexico, India, Bulgaria, and Spain revealed not only the presence of Proteobacteria in the crystalliser ponds (280%–440‰ of salinity), but also that they were more abundant than Bacteroidetes [ 23 , 27 , 33 , 35 , 38 , 39 ]. In addition, in some cases, Actinobacteria was also found among the major phyla harboured by the crystallization ponds [ 32 , 33 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been carried out by culture-independent methods to assess the prokaryotic diversity of MS. However, the majority were based on low-resolution methods (i.e., 16S rDNA clone libraries or Denaturing Gradient Gel Electrophoresis, DGGE) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], which returned a limited vision of the diversity, affecting also community structure analysis. In addition, the majority of the investigations are based on one-time sampling [ 17 , 18 , 19 , 21 , 23 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], generating scant information on the prokaryotic taxa fluctuations over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial diversity at BSF is comparable to that of other dry saline environments. Archaeal communities are often dominated by members of Halobacteria (4244). Bacterial communities are often dominated by Bacteroidetes ( Salinibacter ) and Proteobacteria (4547).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial diversity at BSF is comparable to that of other dry saline environments. Archaeal communities are often dominated by members of Halobacteriaceae (Di Meglio et al, 2016; Kambourova et al, 2017; Stivaletta et al, 2009). Bacterial communities are often dominated by Bacteroidetes ( Salinibacter ) and Proteobacteria (Rasuk et al, 2014; Stivaletta et al, 2011; Vogt et al, 2017).…”
Section: Disscusionmentioning
confidence: 99%